Ribosomal modification protein rimK-like family member A activates betaine-homocysteine S-methyltransferase 1 to ameliorate hepatic steatosis - Han Yan; Wenjun Liu; Rui Xiang; Xin Li; Song Hou; Luzheng Xu; Lin Wang; Dong Zhao; Xingkai Liu; Guoqing Wang; Yujing Chi; Jichun Yang (Signal Transduction and Targeted Therapy)
Abstract Nonalcoholic fatty liver disease (NAFLD) is a serious threat to public health, but its underlying mechanism remains poorly understood. In screening important genes using Gene Importance Calculator (GIC) we developed previously, ribosomal modification protein rimK-like family member A (RIMKLA) was predicted as one essential gene but its functions remained largely unknown. The current study determined the roles of RIMKLA in regulating glucose and lipid metabolism. RIMKLA expression was reduced in livers of human and mouse with NAFLD. Hepatic RIMKLA overexpression ameliorated steatosis and hyperglycemia in obese mice. Hepatocyte-specific RIMKLA knockout aggravated high-fat diet (HFD)-induced dysregulated glucose/lipid metabolism in mice. Mechanistically, RIMKLA is a new protein kinase that phosphorylates betaine-homocysteine S-methyltransferase 1 (BHMT1) at threonine 45 (Thr45) site. Upon phosphorylation at Thr45 and activation, BHMT1 eliminated homocysteine (Hcy) to inhibit the activity of transcription factor activator protein 1 (AP1) and its induction on fatty acid synthase (FASn) and cluster of differentiation 36 (CD36) gene transcriptions, concurrently repressing lipid synthesis and uptake in hepatocytes. Thr45 to alanine (T45A) mutation inactivated BHMT1 to abolish RIMKLA’s repression on Hcy level, AP1 activity, FASn/CD36 expressions, and lipid deposition. BHMT1 overexpression rescued the dysregulated lipid metabolism in RIMKLA-deficient hepatocytes. In summary, RIMKLA is a novel protein kinase that phosphorylates BHMT1 at Thr45 to repress lipid synthesis and uptake. Under obese condition, inhibition of RIMKLA impairs BHMT1 activity to promote hepatic lipid deposition.